2015
DOI: 10.1007/s11356-015-5163-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation along the year of trace metal levels in the compartments of the seagrass Posidonia oceanica in Port El Kantaoui, Tunisia

Abstract: The accumulation of the five trace metals (TMs) cadmium, copper, lead, nickel and zinc was measured in Posidonia oceanica leaves. Shoots were seasonally sampled at 8-10-m depth from four stations located in Port El Kantaoui area, Tunisia, during four campaigns performed in 2012. Levels of the five TMs were analyzed using inductively coupled plasma atomic emission spectrometry (ICP-AES) in three compartments of P. oceanica shoots: blades and sheaths of adult leaves and intermediate leaves. Results showed a pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Similar correlations were reported in the previous studies (Lafabrie et al 2008;Zakhama-Sraieb et al 2016;Bravo et al 2016).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar correlations were reported in the previous studies (Lafabrie et al 2008;Zakhama-Sraieb et al 2016;Bravo et al 2016).…”
Section: Resultssupporting
confidence: 92%
“…oceanica in previous research (Warnau et al 1995;Baroli et al 2001;Lafabrie et al 2008;Serrano et al 2011;Ferrat et al 2012;Di Leo et al 2013;Zakhama-Sraieb et al 2016;Saliha et al 2016;Bonanno and Di Martino 2017;El Zrelli et al 2017;Zeghdoudi et al 2019). However, Cr and Pb were the only elements that concentrations were generally found higher compared to previously reported data (Table 4).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The variability of assemblages and biomass founded in the present study agrees with those described for P. oceanica meadows in the southern coast of Tunisia by Ben Brahim et al [25,36] and by Mabrouk et al [20] in the region of Mahdia eastern coast of Tunisia, where biomass of macro-epiphytes on leaves of P. oceanica was high in summer and low in winter. Similar results were reported by Zakhama-Sraieb et al [37] in Port El Kantaoui, Tunisia where summer appears a sensitive season marked by the high development and dominance by encrusting Corallinaceae and opportunistic macroalgal species which can reach high cover. Moreover, the epiphyte load and percentage cover of assemblages of different taxa were similar and no variability between the different sites was detected.…”
Section: Discussionsupporting
confidence: 89%
“…A study reported by Bonanno and Martino (2017) and Llagostera et al (2011) also showed the same findings using seagrass P. oceanica and C. nodosa, respectively. Leaves of seagrass accumulated metals including Cd not only from roots translocation but also perform a higher absorption rate of the dissolved metals from surrounding waters (Rosalina et al 2019;Zakhama-Sraieb et al 2015). This result also indicated that there is a removal strategy conducted by seagrass species by storing the amount of metals in the leaves and then performed metal reduction because of a high rate of alteration in the leaves of seagrass (Bonanno & Martino 2017).…”
Section: Metal Concentrations and Distributions In Sediments And Seagmentioning
confidence: 89%